2005
DOI: 10.1007/s10350-004-0898-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Fistulas-in-Ano With Fibrin Sealant in Combination With Intra-adhesive Antibiotics and/or Surgical Closure of the Internal Fistula Opening

Abstract: Treatment of fistula-in-ano with fibrin sealant with closure of the internal opening was somewhat more successful than sealant with cefoxitin or the combination, however this did not achieve statistical significance. None of the three modifications were more successful than historic controls at our institution treated with sealant alone. Therefore, the addition of intra-adhesive cefoxitin, closure of the internal opening, or both are not recommended modifications of the fibrin sealant procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
6

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 49 publications
1
53
0
6
Order By: Relevance
“…However, we do believe that infection and increased rectal pressure during defecation may potentially contribute to failure. Singer et al 17 randomized 75 patients into three groups: instillation of fibrin glue with suture closure of the internal opening; fibrin glue with intra-adhesive antibiotics; and fibrin glue with both closure of the internal opening and intra-adhesive antibiotics. There were no significant differences in the success rate among the groups, and none of these modifications were more successful than historic controls treated with glue alone by the same surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do believe that infection and increased rectal pressure during defecation may potentially contribute to failure. Singer et al 17 randomized 75 patients into three groups: instillation of fibrin glue with suture closure of the internal opening; fibrin glue with intra-adhesive antibiotics; and fibrin glue with both closure of the internal opening and intra-adhesive antibiotics. There were no significant differences in the success rate among the groups, and none of these modifications were more successful than historic controls treated with glue alone by the same surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 More recent studies have investigated modifications of the technique in the attempt to improve results. 7,9 Investigators have cited incomplete filling of the fistula tract because of cavitary fistula tracts or the presence of side branches extending from the fistula tract as a cause of fistula recurrence after fibrin sealant obliteration. 5,12 Lindsey et al 12 reported the efficacy of endorectal ultrasound to identify fistula cavities and side branches and perhaps the use of this modality in the preoperative assessment will improve outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, more recent studies have failed to achieve the results reported in earlier studies and have led many to question the usefulness of the technique. [7][8][9][10][11][12] Advancement flaps are another option for the treatment of complex anal fistulas. They cover the primary opening, do not divide the sphincter, and can be combined with overlapping sphincter reconstruction for anterior fistulas in females.…”
mentioning
confidence: 99%
“…Although the majority of studies have reported a 31%-60% success rate in the healing of CD perianal fistulae following treatment with fibrin glue, 84,87,88,95,96 a recent study by Singer et al 97 found treatment of fistula with fibrin glue failed in all CD patients included in the study. Moreover, although Vitton et al 98 reported closure of perianal fistulae in 71% of CD patients 3 months after treatment, endosonographic evaluation confirmed complete closure of the fistula tract in only 14% of patients.…”
Section: Biological Gluesmentioning
confidence: 96%